Spatiotemporal evolution patterns of mining-induced overburden damage based on microseismic event response analysis - Yang, Xiao; Shi, Longqing; Qiu, Mei; Han, Jin; Qu, Xingyue; Fu, Song (Journal of applied geophysics, 2025)
Jurassic coal mining in the Ordos Basin faces threats from overlying water-bearing sandstone layers of the Yijun and Luohe Formations, posing challenges for predicting the dynamic evolution prediction of spatial relationships between water-conducting fracture zones and aquifers. This study integrated rock beam theoretical models with microseismic monitoring data to analyze the spatiotemporal evolution of overburden fracture characteristics during longwall face retreat. Through mechanical model analysis of the overburden, we elucidated the stress-driving mechanism of individual rock beams in the mining direction (transverse), thereby establishing a longitudinal “four-zone” structural model of overburden fracture (Collapsed water-conducting zone, Rock-beam water-conducting zone, Damaged rock-beam weak-permeability zone, and Initial water-resisting zone), identifying the upper boundary of water-conducting fracture zone as the damaged rock-beam weak-permeability zone. Taking Longwall Face 1502 of Shaozhai Coal Mine as the research object, spatiotemporal analysis of microseismic data during production revealed that microseismic frequency time series exhibited a fluctuating decreasing trend and dynamically responded to rock beam fracture characteristics. Based on this, we applied singular spectrum analysis coupled with a distance-weighted energy algorithm to process microseismic data, identifying significant overburden fracture changes at 74, 197, 320, and 432 days of face advancement. By integrating coal measures depositional environments, microseismic event density, and stratigraphic columns, we dynamically determined the overburden fracture boundary and maximum development of the water-conducting fracture zone extended to the 37.46 m mudstone layer of the Anding Formation. Validation through water injection tests confirmed that the Yijun and Luohe Formations remained within the Initial water-resisting zone, undisturbed by mining activities. The ternary analysis method of “stress field driving → microseismic response → sedimentary constraint” proposed in this study reveals the dynamic correlation between mining-induced overburden fracture and microseismic responses, providing a theoretical foundation for effective water prevention and control measures. •Established a longitudinal “four-zone” structural model of overburden fracture.•Overburden model based on water conductivity characteristics.•Identified characteristic advance distances using singular spectrum analysis methods.•Determined WCFZ height through microseismic event response analysis.•Proposed “stress-response-constraint” framework for overburden fracture analysis.•Validated hazardous aquifers remain undisturbed in the initial water-resisting zone.